Microstructural, mechanical, in vitro corrosion and biological characterization of an extruded Zn-0.8Mg-0.2Sr (wt%) as an absorbable material - Čapek, Jaroslav; Kubásek, Jiří; Pinc, Jan; Fojt, Jaroslav; Krajewski, Stefanie; Rupp, Frank; Li, Ping (Materials science & engineering. C, Materials for biological applications, 2021)
Zinc (Zn) alloys seem to be promising candidates for application in orthopaedic or cardiovascular medical implants. In this area, high standards are required regarding the biocompatibility as well as excellent mechanical and tailored degradation properties. In the presented study, a novel Zn-0.8Mg-0.2Sr (wt%) alloy has been fabricated by the combination of casting, homogenization annealing and extrusion at 200 °C. As a consequence of its fine-grained homogenous microstructure, the prepared material is characterized by an excellent combination of tensile yield strength, ultimate tensile strength and elongation corresponding to 244 MPa, 324 MPa and 20% respectively. The in vitro corrosion rates of the Zn-0.8Mg-0.2Sr alloy in the physiological solution and the simulated body fluid were 244 μm/a and 69.8 μm/a, respectively. Furthermore, an extract test revealed that Zn-0.8Mg-0.2Sr extracts diluted to 25% had no adverse effects towards L929 fibroblasts, TAg periosteal cells and Saos-2 osteoblasts. Moreover, the Zn-0.8Mg-0.2Sr surface showed effective inhibition of initial Streptococcus gordonii adhesion and biofilm formation. These results indicated the Zn-0.8Mg-0.2Sr alloy, which has superior mechanical properties, might be a promising candidate for materials used for load-bearing applications.
Keywords: Biocompatible Materials; Absorbable metals; Zinc; vstřebatelné implantáty; Tensile Strength; koroze; Mechanical properties; Corrosion; Degradation behaviour; biokompatibilní materiály; Antibacterial property; Cytotoxicity; Absorbable Implants; pevnost v tahu; zinek; slitiny; Alloys; testování materiálů; Materials Testing